Evaluation of Elementary Students’ Attitudes Toward Science as a Result of the Introduction of an Enriched Science Curriculum - Nadirova, Anna; Burger, John (Alberta Journal of Educational Research, 2008)
One of the challenges facing school educators is motivating students to learn science. This study is part of an evaluation of enriched science curriculum introduced in five western Canadian (Alberta) urban schools. The objective was to develop a multidimensional instrument suitable for evaluating the attitudes of students toward science with a potential to be used for classroom assessments. The study addressed instrument validity and reliability by testing a 40-item questionnaire using data from grade 4 students. The six-factor solution provided a conceptual foundation for future studies and instrument refinement. Overall, students who had been learning the experimental curriculum for three years displayed more positive attitudes toward science than control students.